Application of allylic amine formation from aziridine-2-ol under appel reaction condition: synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester - Chavan, Subhash P.; Kawale, Sanket A.; Patil, Niteen B.; Kalbhor, Dinesh B. (Tetrahedron Letters, 2021)
PPh3/I-2/imidazolde mediated allyl amine formation from aziridine-2-alcohol was explored for the synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester. (C) 2021 Published by Elsevier Ltd.
Keywords: Allyl amine; Aziridine-2-alcohol; Aziridinium ion; Birch reaction; Ring opening